(untitled) (Concept: The Journal of Contemporary Community Education Practice Theory, 2016)
In past years, a number of writers – including Astra Taylor, Cory Doctorow, Howard Rheingold, Christian Fuchs, and others – have published important books about the dynamics of the social media. Yet, Thomas Allmer has managed to find a unique standpoint that provides his book with a much-deserved place in this somewhat cluttered research space. Based on a combination of in-depth theoretical inquiry and sound quantitative research, Critical Theory and Social Media addresses issues pertaining to theory and practice in equal depth – thus walking the walk of critical social praxis.